South African religious demography: The 2013 General Household Survey - Schoeman, Willem J. (HTS teologiese studies, 2017)
The South African religious landscape is diverse and has a profound effect on the role that faith communities may and should play within this context. The General Household Survey (2013), conducted by StatsSA, gave, for the first time since the census of 2001, a picture of the South African religious profile. The aim is to use religious affiliation and adherence as indicators to plot this landscape. These indicators provide a framework to define and explore the role of the church and faith communities in the South African society. How should secularisation, evangelism, social engagement and the prophetic voice of the church be viewed within this context? The aim of this article is to explore these and other questions within the 2013 General Household Survey as a demographical framework to describe a South African reality for faith communities.